1998
DOI: 10.2307/4003200
|View full text |Cite
|
Sign up to set email alerts
|

Using a Grazing Pressure Index to Predict Cattle Damage of Regenerating Tree Seedlings

Abstract: This research investigated the potential for using cattle grazing pressure (AU Mg-' ha-') and stocking rate (Animal Unit Days ha-') for predicting basal scarring and browsing of lodgepole pine (pinus conforta Dot@) seedlings on cutblocks in southern British Columbia from 1989 to 1992. Cattle browsing on lodgepole pine seedlings occurred almost exclusively during the fit 2 years of grazing. Browsing increased (P c 0.05; 3= 0.71) with increasing stocking rate only during the first year of grazing. Browsing incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Other plantation studies have found that cattle can either increase or decrease growth rates of tree seedlings depending on the system and stocking rates (Pitt et al, 1998;Karl and Doescher, 1993;Ramirez-Marcial, 2003). In this study, herbicide application and cattle exclusion had positive effects on the growth and survival of planted tree seedlings.…”
Section: Experimental Treatmentsmentioning
confidence: 46%
“…Other plantation studies have found that cattle can either increase or decrease growth rates of tree seedlings depending on the system and stocking rates (Pitt et al, 1998;Karl and Doescher, 1993;Ramirez-Marcial, 2003). In this study, herbicide application and cattle exclusion had positive effects on the growth and survival of planted tree seedlings.…”
Section: Experimental Treatmentsmentioning
confidence: 46%
“…In addition to being browsed, almost all large saplings showed clear basal scarring due to trampling (C. Vandenberghe personal observation) (cf. Pitt et al 1998), but none of the saplings were broken. This study was conducted under unusually dry weather conditions and the amount of browse consumed by cattle is likely to vary with weather conditions and forage availability (Pollock et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…The consumption of woody plants increases when high quality forage is unavailable, often under dry weather conditions (Holechek et al 1982;OwenSmith and Cooper 1987;Fritz et al 1996) or in late summer (Leloup et al 1996). Tree sapling damage and mortality also increases with grazing pressure (Pitt et al 1998;Hall et al 1992), a result of increased consumption or trampling. In the wooded pastures of the Swiss Jura Mountains, four common tree species, including two conifers (Abies alba and Picea abies) and two deciduous species (Acer pseudoplatanus and Fagus sylvatica), co-occur between an altitude of 800 and 1,200 m. Picea abies is currently dominant.…”
Section: Introductionmentioning
confidence: 99%
“…Livestock were attracted to tame pasture areas. In the absence of proper management, they may have tended to graze these areas to the exclusion of all other native plant areas until the tame forage resource was consumed (Pitt et al 1998, Hincz 2007. The data showed that the greatest change in the time spent was between the tame pasture zone and the 25 m buffer zone.…”
Section: Conclusion 361 Bear Mountainmentioning
confidence: 98%
“…This behaviour was replicated over the four years demonstrating high grazing fidelity. Some of the possible reasons for the observed fidelity were that livestock are attracted to tame pasture, and in many natural regions, will in the absence of active management, graze these areas to the exclusion of all other plant communities until the tame forage resource was depleted (Hincz 2007, Pitt et al 1998). There were some significant differences in usage between pastures to increase dry matter productivity of that land or cause a shift towards higher yielding and more nutritious forage species (Kirychuk et al 2002).…”
Section: Conclusion 361 Bear Mountainmentioning
confidence: 99%